Fiscal Policy and Employment in Advanced and Emerging Economies. (Policy Papers; Policy Paper, 2012)
This paper discusses tax and expenditure policy reforms to raise employment. Using data for 58 advanced and emerging economies, the paper provides a unified assessment of tax and expenditure measures that have usually been addressed separately. The focus is on incentives to increase labor demand and supply rather than on the impact of fiscal policy on employment through aggregate demand effects. It also discusses policies to improve the matching of labor supply and demand, and the principles which should guide the design of country-specific fiscal reforms to boost employment. A comprehensive set of tables on fiscal policies and labor market outturns for advanced and emerging economies is provided, permitting cross-country comparisons to facilitate the design of reform strategies.